Biophysical Studies of TOAC Analogs of the Ctx(Ile21)-Ha Antimicrobial Peptide Using Liposomes - Vicente, Eduardo Festozo [UNESP]; Basso, Luis G. M.; Crusca Junior, Edson [UNESP]; Roque-Borda, Cesar A. [UNESP]; Costa-Filho, Antonio J.; Cilli, Eduardo Maffud [UNESP] (Springer Nature, 2022)
Antimicrobial peptides (AMP) are innate components of the defense system of many forms of life, composing the first line of defense from invading pathogens. Among many AMPs described in several databases, the Ctx(Ile21)-Ha antimicrobial peptide has been proven as a very promising molecule for applications in different areas. Nonetheless, there is still a lack of information about the interactions between the peptide and the different lipid components of the membrane. In this way, this study presents a biophysical approach using circular dichroism, fluorescence, and electron spin resonance (ESR) to analyze how the interactions of the Ctx(Ile21)-Ha antimicrobial peptide and its TOAC-labeled analogs with specific phospholipid head groups can modulate structure, peptide dynamics, and membrane integrity. As a result, Ctx(Ile21)-Ha and its analogs showed a higher affinity for phosphatidylethanolamine (PE) head groups than sphingomyelin (SM), adopting α-helical coiled-coil structures in PE membranes, but not in SM membranes. ESR data indicated that all peptides bind to the liposomes to different extents. The present results help to understand the conformational and dynamical changes of the Ctx(Ile21)-Ha peptide modulated by membranes of different lipid compositions and corroborate the barrel-stave model as the mechanism of action of the Ctx(Ile21)-Ha.
Keywords: Antimicrobial peptide; CD; EPR; Fluorescence; Peptide membrane interaction; Phospholipid head group